Determinatiom of 8-Hydroxy 2′-Deoxyguanosine Using Electrodes Modified with a Dispersion of Carbon Nanotubes in Polyethylenimine - Gutiérrez, Alejandro (2011)
Hydroxyl radicals easily oxidize biomolecules such as proteins and DNA. The most abundant oxidative product of DNA is 8-hydroxy 2?-deoxyguanosine (8-OHdG) and this is considered a biomarker of oxidative DNA damage. This work studies the electrochemical behavior of 8-OHdG on electrodes modified with carbon nanotubes dispersed in polyethylenimine. The technique of differential pulse anodic stripping voltammetry (DPASV) enables quantification of 8-OHdG in the presence of its major interferents, such as ascorbic acid and uric acid. We obtained linear calibration plots in the range from 5.0x10-7 M to 3.0x10-5 M, with detection limit (DL) of 1.0x10-7 M and the quantification limit (QL) of 3.0x10-7 M.